Information Vs. Misinformation on Digital Media: A Study on the Youth of Lahore, Pakistan - Rubab Musarrat (Journal of Peace, Development and Communication, 2022)
The usage of digital media is tremendously increasing with time in Pakistan. According to the latest stats, in 2021 there were 46 million digital media users in Pakistan. The number of digital media users in Pakistan increased by 9.0 million between 2020 and 2021 and in January 2022 there were 71.70 million digital media users in Pakistan. Although digital media has played an important role in Pakistan in recent years on the other hand it is a double-edged sword. On one side it is providing information, awareness, and entertainment at ease and at low cost but on the other hand, due to lack of gatekeeping it is also acting as a source of fake news and misinformation. To study the problem of fake news on digital media platforms the researchers surveyed 200 respondents and analyze the data through SPSS. This study concluded that whether intentionally of unintentionally, people spread fake news on all major digital media platforms in Pakistan.